The Effect of Biofeedback Therapy on Anorectal Function After the Reversal of Temporary Stoma When Administered During the Temporary Stoma Period in Rectal Cancer Patients With Sphincter-Saving Surgery: The Interim Report of a Prospective Randomized Controlled Trial - Kye, Bong-Hyeon (Medicine (Baltimore), 2016)
We evaluated the effect of biofeedback therapy (BFT) on anorectal function after stoma closure when administered during the interval of temporary stoma after sphincter-preserving surgery for rectal cancer. Impaired anorectal function is common after lower anterior resections, though no specific treatment options are currently available to prevent this adverse outcome. Fifty-six patients who underwent neoadjuvant chemoradiation therapy after sphincter-preserving surgery with temporary stoma were randomized into 2 groups: group 1 (received BFT during the temporary stoma period) and group 2 (did not receive BFT). To evaluate anorectal function, anorectal manometry was performed in all patients and subjective symptoms were evaluated using the Cleveland Clinic Incontinence Score. The present study is a report at 6 months after rectal resection. Forty-seven patients, including 21 in group 1 and 26 in group 2, were evaluated by anorectal manometry. Twelve patients (57.1%) in group 1 and 13 patients (50%) in group 2 were scored above 9 points of Cleveland Clinic Incontinence Score, which is the reference value for fecal incontinence (P = 0.770). With time, there was a significant difference (P = 0.002) in the change of mean resting pressure according to time sequence between the BFT and control groups. BFT during the temporary stoma interval had no effect on preventing anorectal dysfunction after temporary stoma reversal at 6 months after rectal resection. However, BFT might be helpful for maintaining resting anal sphincter tone (NCT01661829).